Open Access through the Depot - Hubbard, Bill (Association of Librarians and Information Professionals in the Social Sciences, 2007)
The mission of "the Depot" is to provide a service that enables all UK academics to share in the benefits of open access exposure for their post-print research outputs. It does this by providing a national intake and storage facility - the Depot - for use by any UK academic in Higher Education. This article describes the Depot and the service it provides.